Early Basal Cortisol Level as a Predictor of Hypothalamic-Pituitary-Adrenal (HPA) Axis Function After Pituitary Tumor Surgery - Polovina, Tanja Skoric; Kraljevic, Ivana; Solak, Mirsala; Balasko, Annemarie; Haxhiu, Arta; Haxhiu, Arita; Dusek, Tina; Poljicanin, Tamara; Kastelan, Darko (Experimental and Clinical Endocrinology & Diabetes, 2019)
Purpose The purpose of this study was to evaluate the clinical relevance of the early postoperative basal cortisol level in assessing the postoperative hypothalamic-pituitary-adrenal (HPA) axis function after pituitary tumor surgery.Methods We performed a prospective observational study that enrolled 83 patients operated for pituitary adenoma or other sellar lesions at the University Hospital Center Zagreb between December 2013 and April 2017 (44 nonfunctioning pituitary adenomas, 28 somatotropinomas, 5 craniopharyngiomas, 2 prolactinomas resistant to medical therapy and 4 other lesions - Rathke's cleft cyst, arachnoid cyst, chondroma and gangliocytoma). Exclusion criteria were Cushing's disease, chronic therapy with glucocorticoids prior to surgery and preoperative adrenal insufficiency. Early postoperative basal cortisol levels (measured on the second postoperative day) and the Synacthen stimulation test (performed 3 months after the surgery with the peak cortisol level of>500 nmol/L considered as a normal response) were analyzed to assess HPA axis function during follow-up.Results ROC analysis showed a cut-off of the basal cortisol level of ≥300 nmol/L measured on the second postoperative day to predict normal postoperative HPA axis function with the sensitivity of 92.31%, specificity of 87.14% and positive predictive value of 57.14%.Conclusion The basal cortisol level on the second postoperative day is a valuable tool to predict integrity of the HPA axis after pituitary tumor surgery. Our data suggest that the cortisol level of ≥300 nmol/L accurately predicts adrenal sufficiency and that in these patients glucocorticoid therapy can be withdrawn.
Keywords: hypocortisolism; glucocorticoid replacement; transsphenoidal; transcranial surgery